2015
DOI: 10.1093/mnrasl/slv053
|View full text |Cite
|
Sign up to set email alerts
|

ALMA observations of 99 GHz free–free and H40α line emission from star formation in the centre of NGC 253

Abstract: We present Atacama Large Millimeter/submillimeter Array observations of 99.02 GHz freefree and H40α emission from the centre of the nearby starburst galaxy NGC 253. We calculate electron temperatures of 3700-4500 K for the photoionized gas, which agrees with previous measurements. We measure a photoionizing photon production rate of(3.2 ± 0.2) × 10 53 s −1and a star formation rate of 1.73 ± 0.12 M ⊙ yr −1 within the central 20×10 arcsec, which fall within the broad range of measurements from previous millimetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 28 publications
6
79
1
Order By: Relevance
“…If no rotation was included in the derivation of the relation between SFR and Q, the coefficient in Equation 11 would be very similar to the Murphy et al (2011) coefficient. The additional difference between the Kennicutt (1998) and Bendo et al (2015b) coefficients is related to the difference between the Kennicutt (1998) and Murphy et al (2011) coefficients. As discussed by Calzetti et al (2007), this could be attributed to assumptions regarding the IMF and star formation history.…”
Section: Star Formation Rates From Alma Datamentioning
confidence: 96%
See 2 more Smart Citations
“…If no rotation was included in the derivation of the relation between SFR and Q, the coefficient in Equation 11 would be very similar to the Murphy et al (2011) coefficient. The additional difference between the Kennicutt (1998) and Bendo et al (2015b) coefficients is related to the difference between the Kennicutt (1998) and Murphy et al (2011) coefficients. As discussed by Calzetti et al (2007), this could be attributed to assumptions regarding the IMF and star formation history.…”
Section: Star Formation Rates From Alma Datamentioning
confidence: 96%
“…Peel et al 2011), synchrotron and thermal dust emission could contribute a significant fraction of the emission at this frequency (e.g. Bendo et al 2015b). To use the continuum emission to estimate both Te and SFR, we need to remove the other continuum emission sources from the free-free emission.…”
Section: Spectral Energy Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution could account for up to 20% of 353 GHz continuum flux density, which is estimated by extrapolating the 99 GHz free-free flux density given by Bendo et al (2015). Note that, however, this estimate is just an upper-limit, since the observations conducted by Bendo et al (2015) covered the emission from larger spatial scale than we do, as the minimum baseline length of their observations (7.0kλ; Bendo et al 2015) is half as long as that of ours (15.3kλ). Although the estimate of dust masses of the clumps presented in Table 1 needs to be slightly reduced, the correction up to 20% does not affect the comparison of the scales of the clumps.…”
Section: Line Profiles and Emission Parametersmentioning
confidence: 99%
“…, and the star formation rate is ∼5 M e yr −1 (Lenc & Tingay 2006;Rampadarath et al 2014;Bendo et al 2015;Lucero et al 2015). It has been suggested that up to half of the radio sources in the central starburst region are dominated by thermal emission, i.e., H II regions characterized by a flat radio spectral index 24 α;0.1 and including at least one large supercluster of stars (Ulvestad & Antonucci 1997;Keto et al 1999).…”
Section: Introductionmentioning
confidence: 99%